Antioxidant and phytochemical properties and in vitro cancer chemopreventive effects of averrhoa bilimbi l. extract on human breast and cervical adenocarcinoma - Yan, See Wan (2012)
High consumption of fruits has been associated with a reduced risk of various degenerative diseases such as cancer. These protective properties are reckoned to be linked to the micronutrients and non-nutritive phytochemicals present in fruits. This study was conducted to investigate the nutritional compositions, total phenolic and flavonoid contents, antioxidant capacity, antioxidant vitamins, phenolic acid and flavonoid compounds, as well as anticancer potential of two types of fruits endemic to Malaysia: Averrhoa bilimbi (bilimbi) and Averrhoa carambola (carambola). Commonly consumed among the locals, these underutilized fruits have been popularly practiced as folk medicine since ancient times. Results from nutritional compositions analyses showed that bilimbi possessed higher fat and total dietary fibre but comparable moisture, ash, carbohydrate and protein content with that of carambola. Results from Folin-Ciocalteu, aluminium chloride colourimetric assays and antioxidant vitamins analyses indicated a higher antioxidant vitamins and flavonoid content in bilimbi while carambola with higher total phenolic. β-carotene bleaching and DPPH radical scavenging assays suggested that carambola displayed stronger antioxidant capacity and was positively correlated with its total phenolic content. The presence of non-nutritive phytochemicals in both fruits was evaluated by HPLC analysis based on the optimized extraction conditions performed through single-factor experiments. Analysis revealed that optimal extraction conditions were 80% ethanol at 65 ºC for 8 hours in both fruit extracts. Phenolic compounds extracted by the optimal extraction conditions were subjected to HPLC analysis. Epigallocatechin and catechin were identified as the key flavonoids in bilimbi and carambola, respectively while sinapic acid and syringic acid were the predominant phenolic acid in bilimbi and carambola, respectively. Cytotoxic and anticancer potential of bilimbi and carambola ethanolic extracts were examined on various human cancer cell lines (breast, cervical, colon, liver and ovarian adenocarcinoma) as well as non-malignant Chang Liver cell line. Findings from MTS assay implied a 50% growth inhibitory effect induced by bilimbi extract on cervical cancer cell line (HeLa) and non-hormone dependent breast cancer cell line (MDA-MB-231) at 70 and 90 μg/ml, respectively without any cytotoxic effect on non-malignant Chang Liver cell line. In contrast, carambola extract was unable to exert any growth inhibitory effect even concentration was increased up to 200 μg/ml. Further investigations to determine apoptogenic potential of bilimbi extract revealed typical morphological features of apoptosis as well as formation of ladder-like pattern in bilimbi-treated HeLa and MDA-MB-231. Apoptosis and antiproliferative effects were further evidenced with the increased in sub G1 population and accumulation of cells with a 2N DNA content in cell cycle analysis, suggesting perturbation at G0/G1 checkpoint. BrdU incorporation cell proliferation assay indicated a decreased in cells synthesis (S phase). Released of cytochrome c coupled with upregulation of caspase-3/7 and caspase-9 expression indicated that molecular mechanism in the induction of apoptosis by bilimbi on HeLa and MDA-MB-231 was through mitochondria-mediated intrinsic pathway, which also involve upregulation of pro-apoptotic Bax protein and downregulation of anti-apoptotic Bcl-2 protein. Upregulation of tumour suppressor p53 protein was detected in HeLa upon exposure to bilimbi, as opposed to MDA-MB-231 which was found to be independent of p53. Hence, bilimbi induced apoptosis through a p53-dependent mitochondrial pathway in HeLa and a p53-independent mitochondrial pathway in MDA-MB-231. Based on the antioxidant and phytochemicals properties as well as anticancer potential, bilimbi offers a promising candidate for cancer chemoprevention strategy. As a natural product, bilimbi is potentially safe and beneficial for pharmaceutical and health industries worth further research and investigations.